The Influence of Training and Motivation on the Performance of Business Actors in Busmetik with Competence as an Intervening Variable - Diana Kartika Pramodha Wardhani; Sigit Hermawan (Proceedings of The ICECRS, 2021)
Research Objectives to analyze the effect of Training and Motivation on the performance of Busmetik business people with competence as intervening variabell. Training for cosmetic business actors has been routinely followed, however, the shrimp production target is still not optimally achieved. Quantitative methods are used in this study to prove the hypothesis regarding the relationship of research variables namely Training, Motivation, Competence and Performance. The results of the analysis show that training has a significant effect on competence, motivation has a significant effect on competence, training has a significant effect on performance, motivation has a significant effect on performance, competence has a significant effect on performance. The path analysis results show that competency is able to be an intervening variable for training and motivation for performance. Evident from the indirect influence of training and motivation on performance is greater than the direct influence. Furthermore, for the Fisheries Office of Pasuruan Regency as a coach, it is necessary to pay attention to Training, Motivation and Competence in HR management because it affects performance directly or indirectly.